2013
DOI: 10.1590/s1516-35982013001100007
|View full text |Cite
|
Sign up to set email alerts
|

Residual feed intake and hematological and metabolic blood profiles of lle de France lambs

Abstract: -The objectives of this study were to estimate the phenotypic correlations of residual feed intake (RFI) and gross feed efficiency (GFE) with hematological and metabolic blood profiles of lambs and to determine the differences for these traits in animals of different RFI classes. Twenty Ile de France male lambs, 115±8 days of age and 31.3±4.1 kg of body weight (means ± SD), were individually housed and their dry matter intake was measured over 65 days. They were weighed every 13 days to determine the average d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 22 publications
1
14
0
3
Order By: Relevance
“…Plasma creatinine level was negatively associated with fat depth (CLARKE et al, 1996) and was found to be negatively correlated with RFI (HERD and ARTHUR, 2009). Similar to the findings of the present study, PAULA et al (2013) and observed a negative correlation (r = -0.45) between RFI and the mean concentration of serum creatinine, and a comparison of the two RFI groups showed significant differences for this variable. However, no differences in the levels of blood creatinine between the low and high RFI groups were observed by SHARMA et al (2016) andBOSE et al (2014) in Murrah buffalo calves, or by NASCIMENTO et al (2015) in Nellore cattle.…”
Section: A K Singh Et Al: Efficiency Of Calves Varying In Rfisupporting
confidence: 89%
“…Plasma creatinine level was negatively associated with fat depth (CLARKE et al, 1996) and was found to be negatively correlated with RFI (HERD and ARTHUR, 2009). Similar to the findings of the present study, PAULA et al (2013) and observed a negative correlation (r = -0.45) between RFI and the mean concentration of serum creatinine, and a comparison of the two RFI groups showed significant differences for this variable. However, no differences in the levels of blood creatinine between the low and high RFI groups were observed by SHARMA et al (2016) andBOSE et al (2014) in Murrah buffalo calves, or by NASCIMENTO et al (2015) in Nellore cattle.…”
Section: A K Singh Et Al: Efficiency Of Calves Varying In Rfisupporting
confidence: 89%
“…In the livestock sector, this could be achieved by reducing the feed to gain ratio or 'feed conversion rate' (FCR, defined as the amount of feed needed to produce one unit of animal product) which would also reduce the environmental impact of animal farming. As far as lamb production is concerned, a decrease of up to 15% in dry matter intake (DMI) between efficient and inefficient animals to reach a similar target body weight has been demonstrated (de Paula et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…El RFI se obtiene a partir de la diferencia entre el consumo observado y el consumo estimado con el modelo estadístico, de modo que los animales con menor valor RFI son considerados más eficientes porque ingieren menos alimento que el que podría esperarse en régimen ad libitum para un ritmo de crecimiento determinado. En ganado ovino se ha comprobado que los corderos con menor valor RFI (y, por tanto, más eficientes) consumen entre un 11 y un 18% menos de materia seca en el periodo de cebo y tienen una ADG similar a los de mayor RFI (Sharifabadi et al, 2012, de Paula et al, 2013, Liang et al, 2017, Zhang et al, 2017. Teniendo en cuenta que el cebo de corderos ligeros tiene una duración aproximada de 50 días, reducir en 150 g el consumo medio diario de cada cordero manteniendo la misma ADG permitiría ahorrar 7,5 kg de alimento en todo el periodo, disminuyendo significativamente los costes de producción derivados de la alimentación.…”
Section: Medidas De Eficiencia Alimentariaunclassified
“…Los cambios en la composición corporal pueden afectar a la eficiencia alimentaria porque el aumento de peso basado en la deposición de proteína es más eficiente que el obtenido a partir del depósito de grasa. Se ha descrito que los corderos y terneros con menor RFI presentan mayores concentraciones sanguíneas de creatinina (Richardson et al, 2004, Lawrence et al, 2012, de Paula et al, 2013, Fitzsimons et al, 2013, un producto final de la degradación de la creatina que sirve como indicador de la masa muscular . La creatinina está correlacionada negativamente con el grosor de la grasa del lomo ovino (Clarke et al, 1996), por lo que el menor depósito de tejido adiposo observado en el lomo de los corderos más eficientes (Zhang et al, 2017) se encuentra en consonancia con las mayores concentraciones sanguíneas de este metabolito.…”
Section: Factores Que Afectan a La Eficiencia Alimentariaunclassified
See 1 more Smart Citation